Factors influencing job satisfaction among professionals and paramedics - Norsharul Nizam, Yaakub (2025)
Job satisfaction plays a pivotal role in ensuring the efficiency, motivation, and retention of healthcare professionals particularly within the demanding landscape of Malaysia’s public health sector. Despite its importance, healthcare workers often contend with adverse working conditions, including excessive workload, elevated job stress, and compromised work-life balance, all of which may erode their overall satisfaction and professional engagement. This study investigates the influence of job stress, workload, and work-life balance on job satisfaction among healthcare personnel, with a specific focus on physicians, nurses, medical officers, and assistant medical officers serving in public health clinics across Perak. Drawing upon the Job Demands-Resources (JD-R) Theory and Herzberg’s Two-Factor Theory, the study adopts a quantitative, cross-sectional design, surveying 200 respondents through stratified random sampling. Statistical analysis using SPSS version 29.0 revealed that both job stress and workload significantly and negatively predicted job satisfaction, whereas work-life balance emerged as a strong positive predictor. The study’s findings underscore the urgent need for health system stakeholders to implement strategic interventions aimed at mitigating workplace stressors, redistributing workload equitably, and promoting work-life integration to sustain employee well-being and organizational performance. However, the study is limited by its cross-sectional nature and regional scope, which may constrain the generalizability of results across other healthcare contexts. Future research is encouraged to adopt longitudinal and mixed-method approaches, expand the geographical coverage, and examine additional psychosocial and organizational variables to deepen insights into job satisfaction dynamics among healthcare professionals.